MS and COVID-19 challenge: asymptomatic COVID-19 infection during treatment with cladribine - Seferoğlu, Meral (Neurol Sci, 2021)
BACKGROUND: The use of disease-modifying therapies (DMTs) in people with multiple sclerosis (pwMS) may affect COVID-19 infection outcomes due to DMTs’ immunomodulatory and immunosuppressive effects on immune response. The yet unknown issues are both the early response to the infection, as well as the post-infection development of immunity against the virus under these treatments due to their interaction with the immune system. METHODS: We report two asymptomatic cases of COVID-19 in patients with relapsing–remitting multiple sclerosis (RRMS) shortly after starting cladribine therapy, both developed anti-SARS-CoV-2 antibody response. RESULTS: Patients with MS who are under newly initiated treatment with cladribine tablets may experience an asymptomatic COVID-19 infection and they may develop immunity against SARS-CoV-2. CONCLUSION: These observations raise the probability that DMTs with immunosuppressive effects, such as cladribine, may be considered as a treatment option for selected MS patients with high disease activity during the COVID-19 pandemic.